Mitigating the contrail cirrus climate impact by reducing aircraft soot number emissions. Issue 1 (December 2018) - Burkhardt, Ulrike; Bock, Lisa; Bier, Andreas
Abstract Contrail cirrus are a major component of the climate forcing due to air traffic. For a given contrail cirrus cover, ice water content and ice crystal shape, their impact on radiation is dependent on the number and size of ice crystals. Here we use a global climate model to study the impact of a reduction in initially formed ice crystal numbers, as may be caused by reduced soot number emissions. We find that for reduced initial ice crystal numbers the ice water content is decreased and ice crystal sizes increased, leading to a reduction in contrail cirrus optical depth and doubling the fraction of contrail cirrus that cannot be detected by satellite remote sensing. Contrail cirrus lifetimes and coverage are strongly reduced leading to significant reductions in contrail cirrus radiative forcing. The global climate impact of contrail cirrus is nonlinearly dependent on the reduction in initial ice crystal numbers. A reduction in the initial ice crystal number of 80% leads to a decrease in contrail cirrus radiative forcing by 50%, whereas a twofold reduction leads to a decrease in radiative forcing by approximately 20%. Only a few contrail cirrus outbreaks explain a large percentage of the climate impact. The contrail cirrus climate impact can be effectively mitigated by reducing initial ice crystal concentrations in such outbreak situations. Our results are important for assessments dealing with mitigating the climate impact of aviation and discussions about the use of alternative fuels or lean combustion in aviation. Atmospheric science: alternative aviation fuel helps mitigate the contrail climate impact Reducing soot emissions from aircraft by changing the composition of aviation fuels can effectively mitigate the climate impact of contrail cirrus. Ulrike Burkhardt and colleagues from the German Aerospace Centre use a global climate model to estimate the impacts of reduced aircraft soot emissions on properties and the climate forcing of contrail cirrus. Under the low emission condition in which the number of initial ice crystals formed from soot particles is reduced by 80%—a level of reduction that could be obtained using a blend of biofuel and conventional jet fuels—the climate impact of contrail cirrus is estimated to be reduced by 50%. The mitigation effect occurs predominantly in weather conditions that are favourable for contrail cirrus outbreaks: with the same level of reduction in the initial ice crystal number, capturing 25% of those events can reduce 30% of the climate forcing caused by contrail cirrus.